2004
DOI: 10.1016/j.febslet.2004.06.097
|View full text |Cite
|
Sign up to set email alerts
|

P‐REX2, a novel PI‐3‐kinase sensitive Rac exchange factor

Abstract: We have identified an activator of Rac, P-REX2, that is structurally related to the exchange factor PtdIns(3,4,5)-dependent Rac exchanger (P-REX1), but exhibits distinct tissuespecific expression. P-REX2 is spliced into two RNA species, 3.5 and 10 kb in size. The cDNA corresponding to the smaller transcript encodes a protein that exhibits strong similarity with P-REX1 within its N-terminal domains, but differs in the C-terminal region. P-REX2 promoted increased levels of GTP-bound Rac that could be further sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 16 publications
1
89
0
Order By: Relevance
“…PREX2 has been previously reported to act as an inhibitor of PTEN and an activator of the PI3K signaling pathway (15). However, the effect of PREX2 on PTEN and PI3K signaling has never been reported in pancreatic cancer.…”
Section: Promoting Role Of Prex2 In Pancreatic Cancer Cell Migrationmentioning
confidence: 85%
See 2 more Smart Citations
“…PREX2 has been previously reported to act as an inhibitor of PTEN and an activator of the PI3K signaling pathway (15). However, the effect of PREX2 on PTEN and PI3K signaling has never been reported in pancreatic cancer.…”
Section: Promoting Role Of Prex2 In Pancreatic Cancer Cell Migrationmentioning
confidence: 85%
“…PREX2 is able to inhibit the activity of PTEN by directly binding to PTEN through its guanine nucleotide exchange factor domains. Through inhibition of PTEN activity, PREX2 is capable of activating the downstream PI3K signaling pathway (15,16). Indeed, it has been reported that knockdown of PREX2 inhibits the invasion and clonogenicity of gastric cancer cells via inhibition of PI3K signaling (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in the brain, which express P-Rex1 but no GPCR-dependent PI3K), concomitant activation of GPCRs with another class of receptor that couples to protein-tyrosine kinase-regulated PI3K could provide the required P-Rex1 translocation and activation signals. Equally, it seems likely that similar coincidence detection applies to membrane recruitment and activation of the other members of the P-Rex family, P-Rex2 and P-Rex2b (4,5), that are not expressed in hemopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…As phosphatidylinositol 3-kinase has been reported to regulate Rac1 activity through the several guanine nucleotide exchange factors, such as SWAP70 and P-REX2 downstream of Gab1 (53)(54)(55), and Vav and Tiam-1 are also known to mediate Rac1 activity involved in transformation (56, 57), we initially speculated that the implication of Crk in HGF-mediated Rac1 activation may be partial. However, the significant suppression of HGF-dependent activation of Rac1, cell motility, and scattering was shown in Crk knockdown cells, which may suggest the crucial role for Crk in HGF-evoked activation of Rac1 and following cell motility in human synovial sarcoma cells.…”
Section: Discussionmentioning
confidence: 99%